2021
DOI: 10.4314/jasem.v25i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Residential Indoor Radon Assessment in the Vicinity of some Dumpsites in Lagos, Nigeria

Abstract: Dumpsites in Nigeria are generally open and significantly elevate the pollution and contamination level of the total environment.  Indoor radon was measured with CR-39 detectors in some buildings in the vicinity of dumpsites in Lagos, Nigeria. Eight (8) dumpsites (4 dormant and 4 active dumpsites) were chosen for this study. Detectors were exposed in 50 houses randomly selected within 0 and 100m away from the dumpsites. The detectors were exposed for 3 months. They were then retrieved and etched in a 6M NaOH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…All residential buildings and residential buildings and various combination casing materials investigated in this paper are not expected to provide a radioactive hazard to their occupants, according to these indications. Olaoye, et al [17] claim to have used CR-39 detectors to look into the radon levels in both active and inactive dumpsites. For a total of three months, detectors were installed in 50 randomly selected homes that were between 0 and 100 meters from the dumpsites.…”
Section: Radon In Rocks/soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…All residential buildings and residential buildings and various combination casing materials investigated in this paper are not expected to provide a radioactive hazard to their occupants, according to these indications. Olaoye, et al [17] claim to have used CR-39 detectors to look into the radon levels in both active and inactive dumpsites. For a total of three months, detectors were installed in 50 randomly selected homes that were between 0 and 100 meters from the dumpsites.…”
Section: Radon In Rocks/soilsmentioning
confidence: 99%
“…This has significant implications for the small variation noted because of the depreciable levels of concentrations in several houses and inhabited locations mentioned above [6,7]. Using various measurement tools including the Rad7, CR 39, and Pro-3 series detector of radon in houses, places of work, and various campuses in universities, indoor radon and outdoor examinations have been conducted [17,18]. However, there aren't many reports on indoor and outdoor radon implications in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Olaoye, et al [23] in "Residential Indoor Radon Assessment in the Vicinity of some Dumpsites in Lagos, Nigeria" took it to a dump site also. In their expository quest, Eight (8) dumpsites (4 dormant and 4 active dumpsites) were considered.…”
Section: Comparative Survey Of Radon-222 Level In Somementioning
confidence: 99%
“…Two of the radon decay products, Polonium-218 and Polonium-214 , account for vast majority of the radiation exposure to lungs. Exclusive measurements of radon concentrations in dwelling places and homes show that although concentrations may vary widely, radon is universally present, raising concerns that the observed rise in lung cancer cases among the general public could be as a result of radon exposure, especially those who spend a lot hours indoors [23].…”
Section: Relative Impactsmentioning
confidence: 99%
“…Although concentrations can vary greatly, radon is always present, according to independent measurement of radon concentrations in buildings and homes. This raises anxiety in the pragmatic increase in lung disorders such as cancer cases surrounded by wide-ranging public could be due to exposure to radon, particularly for persons who spend their time indoor [17]. Additionally, research has shown that radon has the ability to trigger genetic disorders at any concentration [16].…”
Section: Introductionmentioning
confidence: 99%